2010
DOI: 10.1111/j.1365-2958.2010.07450.x
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoid‐associated PhaF phasin drives intracellular location and segregation of polyhydroxyalkanoate granules in Pseudomonas putida KT2442

Abstract: SummaryThe PhaF is a nucleoid-associated like protein of Pseudomonas putida KT2442 involved in the polyhydroxyalkanoate (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
162
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(171 citation statements)
references
References 53 publications
5
162
0
4
Order By: Relevance
“…Recently, we identified a new PGAP, PhaM, that specifically binds to PHB and to DNA (31). We showed that PhaM is necessary for equal distribution of PHB granules to daughter cells during cell division, similar to PhaF in PHA MCL -accumulating Pseudomonas putida (9). In this study, we observed formation of the first visible granules with attached PhaC1-eYFP within only 5 min after transfer of PHB-free cells to conditions permissive for growth and PHB accumulation (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…Recently, we identified a new PGAP, PhaM, that specifically binds to PHB and to DNA (31). We showed that PhaM is necessary for equal distribution of PHB granules to daughter cells during cell division, similar to PhaF in PHA MCL -accumulating Pseudomonas putida (9). In this study, we observed formation of the first visible granules with attached PhaC1-eYFP within only 5 min after transfer of PHB-free cells to conditions permissive for growth and PHB accumulation (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…Interestingly, recent studies of granule formation in both R. eutropha (36) and Pseudomonas putida (13) have shown that a member of the phasin family in each organism (PhaM and PhaF, respectively) binds nonspecifically to DNA. Thus, in analogy to carboxysome segregation in Synechococcus elongatus (41), granules are equally segregated between daughter cells upon cell division (13), in this case utilizing nonspecific nucleoid binding by granules. Thus, nonspecific interaction of the phasin PhaM with the nucleoid in R. eutropha may explain why granules localized toward the center of the cell.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this phasin binds to DNA nonspecifically through a histone-like domain and plays a key role in intracellular localization and equal distribution of PHA granules to daughter cells during cell division (19,44). Last, PhaP from A. hydrophila (PhaP Ah ) was also observed to act as a positive regulator of the gene that encodes the PHA synthase in this organism, as the overexpression of phaP increased the expression of phaC (45).…”
Section: Role Of Phasins In Pha Metabolismmentioning
confidence: 99%